Impact of Increasing Fertilizer Prices on Productivity and Its Influence on Tobacco Farmers’ Income in Palongan Village - Andrianingsih, Very; Asih, Dessy Novitasari Laras; Hamzah, Amir (PT. Riset Press International, 2024)
New problems have emerged in the agricultural sector related to fertilizer. Fertilizer prices have now increased to twice the previous price. Apart from that, the limited supply of non-subsidized fertilizer is a concern for farmers to continue their farming. Many farmers' land in Palongan Village is starting to be abandoned. The increase in fertilizer prices causes fertilizer to be given at the wrong time, due to the limited capital that farmers have. The impact of this problem is a decrease in tobacco productivity. This can also affect farmer income. The aim of this research is to examine further the impact of increasing fertilizer prices on tobacco productivity and its effect on farmers' income in Palongan Village. Apart from that, to analysis whether there is a difference in the productivity of tobacco farmers before the increase in fertilizer prices and after the increase in fertilizer prices. The method used in this research is the test method paired sample t-test and path analysis. The hypothesis test used is the t-test. Test results paired sample t-test stated that there was a difference in tobacco productivity before and after the increase in fertilizer prices. Test results path analysis stated that the increase in fertilizer prices directly affected tobacco productivity. Meanwhile, indirectly the increase in fertilizer prices through tobacco productivity does not have a significant effect on the income of tobacco farmers.